2013
DOI: 10.1038/srep01859
|View full text |Cite
|
Sign up to set email alerts
|

Polyethyleneimine Incorporated Metal-Organic Frameworks Adsorbent for Highly Selective CO2 Capture

Abstract: A series of polyethyleneimine (PEI) incorporated MIL-101 adsorbents with different PEI loadings were reported for the first time in the present work. Although the surface area and pore volume of MIL-101 decreased significantly after loading PEI, all the resulting composites exhibited dramatically enhanced CO2 adsorption capacity at low pressures. At 100 wt% PEI loading, the CO2 adsorption capacity at 0.15 bar reached a very competitive value of 4.2 mmol g−1 at 25°C, and 3.4 mmol g−1 at 50°C. More importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(172 citation statements)
references
References 38 publications
6
155
1
1
Order By: Relevance
“…However, for chemical adsorption with amine-based adsorbents, CO 2 capacity is mainly affected by the amine content in the adsorbents and there should be no direct relationship between surface area and CO 2 capacity of amine-based chemical adsorption adsorbents, as the CO 2 capacities of these adsorbents result from the reaction with amine groups. For example, it has been found from our research and others' studies that the sample with higher amine loading and lower surface area presents a higher CO 2 adsorption capacity [21,35,36,[86][87][88]. This is explained by that the loaded moieties on the adsorbents' surface could block the pore space of the porous/solid adsorbents [21,35,36].…”
Section: Co 2 Adsorption Performancesmentioning
confidence: 54%
“…However, for chemical adsorption with amine-based adsorbents, CO 2 capacity is mainly affected by the amine content in the adsorbents and there should be no direct relationship between surface area and CO 2 capacity of amine-based chemical adsorption adsorbents, as the CO 2 capacities of these adsorbents result from the reaction with amine groups. For example, it has been found from our research and others' studies that the sample with higher amine loading and lower surface area presents a higher CO 2 adsorption capacity [21,35,36,[86][87][88]. This is explained by that the loaded moieties on the adsorbents' surface could block the pore space of the porous/solid adsorbents [21,35,36].…”
Section: Co 2 Adsorption Performancesmentioning
confidence: 54%
“…These peaks get stronger with the increasing loading PEI due to the hydrophilic surface of PEI. The peaks at 2838 cm À1 clearly observed in the IR spectra of PEI@ZIF-8 samples can be assigned to m (-NH-) stretching vibrations [29], characteristic peak of amine functional groups in PEI. It was observed that the intensity of the peak at 2838 cm À1 increased with an increase in PEI loading.…”
Section: Computational Methodologymentioning
confidence: 94%
“…Lin and Chen et al [29] tried to prepare a PEI incorporated MIL-101, and reported that the resulting composites exhibited obviously enhanced CO 2 adsorption capacity at low pressures, and the adsorption isotherms of CO 2 on dry and humid PEI-MIL-101(Gr) samples were nearly the same, indicating no negative effect of water adsorption on the CO 2 adsorption, which is interesting. However, to the best of our knowledge, the work about functionalization of MOFs with PEI has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Fast adsorption kinetics is one of the most important properties when evaluating a good adsorbent [20][21][22][23]. Currently, a lot of kinetic models are proposed to describe the experimental data.…”
Section: Desorption Kineticsmentioning
confidence: 99%